An anti-inflammatory isoflavone from soybean inoculated with a marine fungus Aspergillus terreus C23-3. Issue 8 (2nd August 2020) - Yang, Jing-Ming; Liu, Ya-Yue; Yang, Wen-Cong; Ma, Xiao-Xiang; Nie, Ying-Ying; Glukhov, Evgenia; Gerwick, Lena; Gerwick, William H; Lei, Xiao-Ling; Zhang, Yi
Abstract: A new isoflavone derivative compound 1 (psoralenone) was isolated from soybean inoculated with a marine fungus Aspergillus terreus C23-3, together with seven known compounds including isoflavones 2 –6, butyrolactone I (7 ) and blumenol A (8 ). Their structures were elucidated by MS, NMR, and ECD. Psoralenone displayed moderate in vitro anti-inflammatory activity in the LPS-induced RAW264.7 cell model. Compound 2 (genistein) showed moderate acetylcholinesterase (AChE) inhibitory activity whereas compounds 2, 5 (biochanin A), 6 (psoralenol), and 7 exhibited potent larvicidal activity against brine shrimp. Compounds 3 (daidzein), 4 (4ʹ-hydroxy-6, 7-dimethoxyisoflavone), and 5 –7 showed broad-spectrum anti-microbial activity, and compound 7 also showed moderate 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity. Graphical abstract: : An anti-inflammatory isoflavone from soybean fermented by a marine fungus Aspergillus terreus C23-3